Massification or Quality of Graduates? A Model for Higher Education and Development in Uganda - Matovu , Musa (African Journal of Education,Science and Technology (AJEST), 2018)
Massification of higher education is inevitable in the development process of Uganda where the country’s Gross Enrollment Ratio (GER) is at 6.8%. Massification in Uganda was introduced with an aim of higher education becoming accessible to all. This paper analyzes the multifaceted debates regarding higher education and development in Uganda. These debates include; (a) massification of higher education leads to development, and (b) training quality graduates leads to development. Against the two debates the government of Uganda has failed to take an appropriate position on whether it is for massification or producing quality of graduates. This literature review answers three broad questions; (i) Does massification of higher education lead to development in Uganda? (ii) Does training of a few quality graduates lead to development in Uganda? And, (iii) what is the best model for higher education in Uganda? With the increasing numbers of students enrolled in higher education institutions higher education has been faced with enormous challenges such as inadequate funding and staffing, deteriorating standards, low quality graduates, high student-staff ratio, poor physical facilities, and insufficient equipment. This paper makes suggestions on how massification in higher education can create a critical mass of human resources that can lead to economic development in Uganda.